2006
DOI: 10.1007/s00223-005-0244-z
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Calcification and Osteoporosis in Men and Postmenopausal Women Are Independent Processes Associated with Aging

Abstract: The objective of this study was to investigate whether low bone mass is directly associated with the severity of coronary atherosclerosis in men and postmenopausal women self-referred for evaluation of coronary atherosclerosis and osteoporosis. Low bone mass was evaluated by measurement of bone mineral density (BMD) using quantitative computerized tomography (QCT). Coronary atherosclerosis was evaluated by measurement of coronary calcium (CC) burden using electron beam computerized tomography (EBCT). Using a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0
12

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 61 publications
3
77
0
12
Order By: Relevance
“…(35) The mechanism of this association is unknown. Studies in the elderly population have found a significant relationship between osteoporosis and mortality in excess, mostly caused by CVD/atherosclerotic diseases (35,36) and frailty syndrome. (37) Beyond the potential cardiovascular confounders, when studying BMD in relation to mortality, it is important to thoroughly investigate whether a low BMD is not merely a marker of underlying illness.…”
Section: Discussionmentioning
confidence: 99%
“…(35) The mechanism of this association is unknown. Studies in the elderly population have found a significant relationship between osteoporosis and mortality in excess, mostly caused by CVD/atherosclerotic diseases (35,36) and frailty syndrome. (37) Beyond the potential cardiovascular confounders, when studying BMD in relation to mortality, it is important to thoroughly investigate whether a low BMD is not merely a marker of underlying illness.…”
Section: Discussionmentioning
confidence: 99%
“…(6) A previous clinical study has shown that patients with self-reported myocardial infarction had significantly higher odds of having low hip bone mineral density (BMD). (7) In addition, the presence of coronary calcifications has been associated with a nonsignificant 8% lower lumbar spine BMD, (8) suggesting that there is an association between subclinical atherosclerosis and lower bone density in the elderly. Recently, it has been reported that cardiovascular disease (CVD), such as congestive heart failure and stroke, is associated with an increase in the risk of subsequent hip fracture, (9) providing further support for such a connection, even if the exact mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Dyslipidemia and chronic inflammation, including the inflammation associated with rheumatoid arthritis, are known to accelerate vascular calcification. Other diseases such as osteoporosis ( 5 ) and diabetes mellitus (DM) ( 6 ) are also associated with vascular calcification. In addition to these conditions, CKD also contributes to vascular calcification, possibly by disturbing calcium and phosphate metabolism ( 7 ).…”
Section: Introductionmentioning
confidence: 99%